2007
DOI: 10.1007/s00192-006-0232-5
|View full text |Cite
|
Sign up to set email alerts
|

Early laparoscopic repair for supratrigonal vesicovaginal fistula

Abstract: Laparoscopic repair of supratrigonal vesicovaginal fistula is less morbid and equally effective compared to open repair. This approach is advisable when transvaginal repair is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
(14 reference statements)
0
14
0
1
Order By: Relevance
“…In these patients, there had been adequate quality tissue for the repair, and all had a successful outcome. There have been reports of successful repair by laparoscopic techniques within 4 weeks following injury [19][20][21].…”
mentioning
confidence: 99%
“…In these patients, there had been adequate quality tissue for the repair, and all had a successful outcome. There have been reports of successful repair by laparoscopic techniques within 4 weeks following injury [19][20][21].…”
mentioning
confidence: 99%
“…[20][21][22] In our series, four of eight (50%) patients had previously undergone unsuccessful open surgery to correct the VVF; this made fistulous tract recognition more difficult because of excessive tissue scarring. We had one conversion (11%) and one failure (12.5%) in the laparoscopic repair of VVF.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, the approach chosen should be that with which the surgeon is most comfortable (5,6) Laparoscopic VVF repair by different approaches has been described. Nezhat et al (7) were the first to report the laparoscopic retrovesical approach in 1994, which decreases the morbidity of the abdominal approach with similar success rates that range from 86% to 100% and minimal surgical trauma, allowing for more rapid convalescence (8,(10)(11)(12)(13)(14)(15)(16). Sotelo et al (8) reported an approach in which the bladder is first intentionally opened, accurately leading to the fistulous tract without requiring additional vaginal incisions or further dissection of the vesicovaginal space.…”
Section: Discussionmentioning
confidence: 99%
“…Once the fistula is identified, the vesicovaginal space is dissected to separate the structures; the importance of this technique lies in the intentional cystotomy for localizing the tract. The laparoscopic approach is primarily associated with similar success rates, minimal surgical trauma and reduced morbidity, allowing for more rapid convalescence (4,8,(10)(11)(12)(13)(14)(15)(16). Despite initial enthusiasm, laparoscopy has not gained popularity, most likely because laparoscopic VVF dissection and intracorporeal suturing are technically challenging.…”
Section: Introductionmentioning
confidence: 99%